Media Studies and the Double Dialectic of Information - Babe, Robert E. (Javnost-The Public, 2011)
As noted elsewhere (Babe 2009, 161-73), information is inherently dialectical. Reflection upon the seminal work of physicist Carl Friedrich von Weizsäcker, however, reveals that information is doubly dialectical. The first part of this article explains and justifies this claim. The second part of the article catalogues various reductionist (non-dialectical) stances toward information, and draws out some of their implications. Confusions, and indeed grievous errors, result from such incompleteness. Finally, the communication theories of Harold Innis and Marshall McLuhan are reviewed briefly as exemplars in ways of forwarding information’s double dialectic.